PROBLEMATIKA PEREMPUAN: PRESENTASI KEKERASAN GENDER PADA CERPEN “LINTAH” DAN “MENYUSU AYAH” KARYA DJENAR MAESA AYU - Rizki Amalia Sholihah (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
Instance of this use of gender violence found in “Lintah” and “Menyusu Ayah” short stories is caused existenceassumption that women are the objects of the society from the violence. Female considered as being number twocan only serve as a means of satisfying men and can not issue an opinion. Besides women's capacity to survive indeterioration and not fighting is the most powerful weapon to make the men feel to win without having to give ameaningful match. Presentation of sexual violence found in short stories